2021
DOI: 10.3390/nano11020393
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Transparent Organic Photovoltaic Cells with Dielectric/Metal/Dielectric Top Electrode: Influence of the Metal on Their Performances

Abstract: In order to grow semi-transparent organic photovoltaic cells (OPVs), multilayer dielectric/metal/dielectric (D/M/D) structures are used as a transparent top electrode in inverted OPVs. Two different electrodes are probed, MoO3/Ag/MoO3 and MoO3/Ag/Cu:Ag/ZnS. Both of them exhibit high transmission in visible and small sheet resistance. Semi-transparent inverted OPVs using these electrodes as the top anode are probed. The active organic layers consist in the SubPc/C60 couple. The dependence of the OPV performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…359 The authors suggested that this enhancement is due to a higher work function of such anode and a better SubPc absorption triggered by the light scattering of ITO/ZnO surface. Additional strategies, such as the use of patterned and multilayer electrodes, 360,361 metallic nanocavities, 362 or ITO treated with O 2 plasma 363 have also yielded promising results. In addition, other studies have been recently devoted to tuning the work function of ITO by physical or chemical functionalization with Langmuir-Blodgett monolayers or benzenesulfonyl chlorides, respectively.…”
Section: Planar-heterojunction (Phj) Solar Cells This Type Of Heteroj...mentioning
confidence: 99%
“…359 The authors suggested that this enhancement is due to a higher work function of such anode and a better SubPc absorption triggered by the light scattering of ITO/ZnO surface. Additional strategies, such as the use of patterned and multilayer electrodes, 360,361 metallic nanocavities, 362 or ITO treated with O 2 plasma 363 have also yielded promising results. In addition, other studies have been recently devoted to tuning the work function of ITO by physical or chemical functionalization with Langmuir-Blodgett monolayers or benzenesulfonyl chlorides, respectively.…”
Section: Planar-heterojunction (Phj) Solar Cells This Type Of Heteroj...mentioning
confidence: 99%
“…DMD designs offer high transparency and conductivity, low turbidity, excellent flexibility, easy fabrication and excellent compatibility with different substrates 24 36 . Therefore, it is clear that ST DMDs have a strong future, especially in ST optoelectronic devices 15 , 20 , 37 40 . An ST DMD electrode is designed to be able to fabricate ultra-thin metallic films and to improve the conductivity and flexibility of indium tin oxide (ITO).…”
Section: Introductionmentioning
confidence: 99%
“…DMD electrodes have taken a vital place in the design of OSC structures as ST. Even if the OSCs are grown over ITO, it is possible to make the opaque top contact transparent and the SC to become ST with the appropriate design of DMD structures 40 . It is noteworthy that DMD structures have simple fabrication processes and simple designs that do not require microscale or nanoscale shaping, such as photonic crystals 42 , 43 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 1,2 ] Furthermore, adequate mechanical flexibility is shown by DMD structured electrodes owing to the good ductility of metals, which also enables the application of DMD electrodes in flexible optoelectronic devices. [ 69 ] Several TCEs based on DMD structure—ZnS/Cu:Ag/WO 3 , [ 70 ] AZO/Ag/AZO, [ 71 ] MoO 3 /Ag/MoO 3 , [ 72 ] ZnS/Cu/Ag/ZnS, [ 73 ] and AZO/AgNW/AZO/ZnO [ 74 ] electrodes were evaluated in this study.…”
Section: Resultsmentioning
confidence: 99%